Development of an Al-Zn-Bi alloy sacrificial anode for the protection of steel in artificial seawater: an electrochemical analysis - M H Qureshi; A Farooq; M Wasim; K M Deen (Materials Research Express, 2024)
The Al-Zn sacrificial anodes are widely used for cathodic protection in marine steel structures. This study evaluates the impact of bismuth addition on the electrochemical properties of the Al-Zn sacrificial anode in artificial seawater. The microstructure analysis confirms the presence of uniformly distributed intermetallic β -AlFeSi and spherical Bi within the α -Al matrix. The open circuit potential (OCP) comparison between Al-Zn-Bi and carbon steel reveals a potential difference of approximately 400 mV, indicating sufficient cathodic protection for the steel. Electrochemical impedance measurements indicate the initial hindered dissolution of the anode due to surface film formation, which later dissociates due to the aggressive attack of Cl ^− species in the electrolyte. The sufficiently negative surface potential (−0.875 V _vs. Ag/AgCl ) observed at 10 mA cm ^−2 demonstrates the suitability of anode for fulfilling the cathodic protection criteria of steel structures.